2018
DOI: 10.3390/ijerph15122815
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Inconsistent Condom Use among Men Who Have Sex with Men (MSM) Who Use Mobile Geo-Social Networking Applications in Greater Tokyo

Abstract: This study examined the prevalence and factors associated with inconsistent condom use among men who have sex with men (MSM) who use gay mobile geo-social networking applications (gay mobile apps) in Greater Tokyo. Among a sample of 1657 MSM recruited through advertisements on gay mobile apps, inconsistent condom use was reported by over one-third (37%) of participants with regular male partners, 18% with casual male partners, and 20% with female partners. In multiple regression analysis, inconsistent condom u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Use of condoms was lower with romantic partners, in about 50% of events. This pattern, whereby condoms are used less often in romantic relationships, has been commonly reported in research with MSM internationally [11][12][13]. Greater familiarity with romantic partners, as well as the desire for increased intimacy, may be key motivators [14].…”
Section: Discussionmentioning
confidence: 74%
“…Use of condoms was lower with romantic partners, in about 50% of events. This pattern, whereby condoms are used less often in romantic relationships, has been commonly reported in research with MSM internationally [11][12][13]. Greater familiarity with romantic partners, as well as the desire for increased intimacy, may be key motivators [14].…”
Section: Discussionmentioning
confidence: 74%
“…Explanatory variables. The study made use of nine explanatory variables that had shown significant associations with consistent condom use during paid sex in previous studies [22, [34][35][36]. These variables were place of residence, wealth quintile, education, age, frequency of reading newspaper, frequency of listening to radio, frequency of watching television, religion, marital status, and employment (see Table 1).…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…Results were presented as adjusted odds ratios with their corresponding 95% confidence intervals to indicate their level of precision. The choice of reference categories at the regression analysis stage was informed by a priori, variable outcome categories with lower frequencies, and previous studies [22, [34][35][36]. Statistical significance was set at p< 0.05.…”
Section: Plos Onementioning
confidence: 99%
“…According to the annual report of HIV/AIDS cases in China, the composition ratio of sexual transmission owing to men who have sex with men (MSM) had increased from 3.4% (2007) to 28.2% (2015) and had stabilized at 28% during 2016 and 2017 [ 1 ]. The high HIV infection rate among MSM was ascribed to high-risk sexual behaviors, such as unprotected anal intercourse (UAI) and inconsistent condom use, through which HIV spread from HIV-positive MSM to general MSM [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%